CRITICAL THINKING PROCESS IN GEOGEBRA-ASSISTED PROBLEM SOLVING - Aniskurnia Rahmadhani Fajerin; Yuli Eko Siswono, Tatag (Universitas Muhammadiyah Metro, 2024)
The development of the world in the 21st century has encouraged the government to improve human resources with the ability to think critically and communicate, especially for students in learning mathematics. However, the fact is that students' critical thinking skills are still low. The purpose of this study was to ascertain how students used the critical thinking when problem solving. Three eighth-grade junior high school students are the subjects of this qualitative case study research design. Critical thinking test and interviews are used to collection data. Following data collection, the phases of data condensation, data presentation, and conclusion drawing. were used to analyze the data. The results showed that: (1) Students in the successful category of the critical thinking process met all indicators for the the critical thinking process, including interpretation, analysis, evaluation, inference, explanation, and self-regulation. (2) Students the less successful category, achieved the indicators of interpretation, analysis, evaluation, and explanation, in their critical thinking processes. Nevertheless, indicators were not met at the inference and self-regulation phases of the critical thinking process. (3) Critical thinking process of students in the unsuccessful category think critically. Students only require the indicators of interpretation for the critical thinking process. Critical thinking process indicators were not met at the phases of analysis, evaluation, inference, explanation, and self-regulation stages, the critical thinking process indicators were not well achieved.